ANALISIS PENGARUH ALIH FUNGSI TROTOAR TERHADAP KENYAMANAN PEJALAN KAKI DI JALAN PALA KOTA MASOHI - Soo, Heider Ali; Amaheka, Sammy. G. M.; Metekohy, Juliet. G. (JURNAL SIMETRIK, 2025)
Sidewalks are one of the supporters of road facilities that are included in misuse. In accordance with Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation, Article 45 paragraph (1) states that supporting facilities for the implementation of traffic and road transportation include sidewalks, bicycle lanes, pedestrian crossings, bus stops, and/or special facilities for people with disabilities, and elderly people. This study aims to identify the transfer of the use of sidewalks by street vendors and see the influence of street vendor activities on pedestrian comfort. The research uses a survey method. The object of the research is the conversion of sidewalks into places for street vendors. Data collection techniques are carried out by observation, questionnaires, and documentation. Data analysis was carried out using validity tests, reliability tests, and multiple linear regression tests. The results of the study show that (1) Side Barriers on Nutmeg Street are Places of Sale and street vendors, (2) the number of forms of function change is dominated by street vendors as many as 22, (3) traders are dominated by food traders as many as 15, (4) the average level of service on the left sidewalk is with LOS B and on the right part is obtained LOS B. The right sidewalk before there is a LOS Obstacle C and after there is an obstacle becomes E, Left Before there is an obstacle, the LOS is B after there is an obstacle, it becomes C Keywords: Functional Transfer, Street Vendors, Sidewalks